Letter from Max Bredig to Kasimir Fajans, April 23, 1944 - Bredig, Max Albert (1944)
Max Bredig (1902-1977) informs his colleague and mentor, Kasimir Fajans (1878-1975), a professor and chemist at the University of Michigan, that his father, Georg Bredig (1868-1944), has passed away.
Keywords: Bredig, Max Albert, 1902-1977; Fajans, Kasimir, 1887-1975; Bredig, Georg, 1868-1944